Penerapan Model Inquiry Based Learning Dalam Meningkatkan Kemampuan Berpikir Kreatif, Sikap Rasa Ingin Tahu, dan Rasa Percaya Diri Pada Pembelajaran Tematik Siswa Kelas K1 di Tingkat Usia Dini [Application of the Inquiry-Based Learning Model in Improving Creative Thinking Ability, Curious Attitude, and Self-Confidence in Thematic Learning for K1 Class Students at Early Age Level] - Siahaan, Totar Septika (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2023)
This research is motivated by the low creative thinking skill, curiosity and self-confidence of K1 students. The purpose of this study was to analyze the application of Inquiry Based Learning model to improve creative thinking, curiosity and self-confidence in K1 students. The type of research used is classroom action research which consists of three learning cycles with the stages of orientation, conceptualization, investigation, conclusion and discussion. The subjects of this study were fourteen students in one class. The instrument used was an assessment rubric to measure creative thinking skills, curiosity and self-confidence. The result showed that there was an increase in the average value of creative thinking in the first cycle is 57,9, in the second cycle is 66,6 and in the third cycle to 78,5. The increase in the average value of curiosity in the first cycle was 47,6 , in the second cycle is 61,8 and in the third cycle to 81,4. The increase in the average of self-confidence in the first cycle is 49,2, in the second cycle is 61,9 and in the third cycle to 82,5. It can be concluded that the Inquiry Based Learning model can improve creative thinking skill, curiosity and self-confidence in thematic learning of K1 students in Early Age Level.